Star Formation History and X-ray Binary Populations: The Case of the Small Magellanic Cloud - Antoniou, V.; Zezas, A.; Hatzidimitriou, D.; Kalogera, V. (2010)
Using Chandra, XMM-Newton, and optical photometric catalogs we study the young X-ray binary (XRB) populations of the Small Magellanic Cloud. We find that the Be/X-ray binaries (Be-XRBs) are observed in regions with star formation rate bursts ~25-60 Myr ago. The similarity of this age with the age of maximum occurrence of the Be phenomenon (~40 Myr) indicates that the presence of a circumstellar decretion disk plays a significant role in the number of observed XRBs in the 10-100 Myr age range. We also find that regions with strong but more recent star formation (e.g., the Wing) are deficient in Be-XRBs. By correlating the number of observed Be-XRBs with the formation rate of their parent populations, we measure a Be-XRB production rate of ~1 system per 3 × 10-3 M sun yr-1. Finally, we use the strong localization of the Be-XRB systems in order to set limits on the kicks imparted on the neutron star during the supernova explosion.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Be; Magellanic Clouds; pulsars: general; stars: early-type; stars: emission-line; stars: formation; X-rays: binaries